2018
DOI: 10.56454/kzcz8297
|View full text |Cite
|
Sign up to set email alerts
|

CPPU (N-(2-chloro-4-pyridinyl)-N’-phenylurea) Enhancement of Cotton Yields

Abstract: The gradual depletion of the Ogallala Aquifer under the Southern High Plains of Texas during the past fifty years has resulted in reduced well capacities for cotton irrigation. Water table declines have already led some to shift from irrigated to dryland farming, and many of the remaining wells cannot provide enough water for full irrigation. The present study evaluated the effectiveness of the synthetic cytokinin CPPU (N-(2-chloro-4-pyridinyl)-N’-phenylurea) on the stimulation of lateral root production and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cytokinins such as 6-BAP are plant hormones involved in growth and development, the regulation of cell division processes, the delay in senescence, and the regulation of apical dormancy [ 24 , 25 ]. It was reported that the application of 6-BAP in selected crops favors the production of buds [ 26 , 27 ] and the generation of roots and flowers [ 28 , 29 ], in addition to the removal of reactive oxygen species [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokinins such as 6-BAP are plant hormones involved in growth and development, the regulation of cell division processes, the delay in senescence, and the regulation of apical dormancy [ 24 , 25 ]. It was reported that the application of 6-BAP in selected crops favors the production of buds [ 26 , 27 ] and the generation of roots and flowers [ 28 , 29 ], in addition to the removal of reactive oxygen species [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%